Do Differences in Spatiotemporal Gait Parameters Predict the Risk of Developing Depression in Later Life? - Briggs, Robert; Kennelly, Sean; Kenny, Rose (My University, 2019)
BACKGROUND/OBJECTIVES: There is growing interest in the association between gait disturbance and depression in later life. The aim of this study is to clarify the longitudinal relationship between specific gait parameters and incident depression within a population-representative sample of older people. DESIGN: Longitudinal analysis of spatiotemporal gait parameters at baseline (wave 1) and incident depression at 2 and 4 years (waves 2/3). Logistic regression models were used to assess the relationship between tertiles of gait parameters and incident depression. SETTING: The Irish Longitudinal Study on Aging. PARTICIPANTS: Over 3600 nondepressed community- dwelling people aged 50 years or older. MEASUREMENTS: A score of 9 or greater on the eight- item Center for Epidemiological Studies Depression Scale at wave 2 or 3 was indicative of incident depression. The GAITRite system was used to measure gait speed, step length, step width, and double support phase during usual speed walking and under dual task conditions. RESULTS: Participants with incident depression (344/3615) had slower gait speed (129.9 [95% confidence interval {CI} = 127.2-132.6] cm/s vs 134.1 [95% CI = 133.0-135.1] cm/s; F = 8.82; P = .003) and shorter step length (68.0 [95% CI = 66.9-69.2] cm vs 70.3 [95% CI = 69.9-70.7] cm; F = 13.99; P < .001) at baseline than those who did not develop depression. Logistic regression models demonstrated that those within the slowest tertile for gait speed and shortest tertile for step length had significantly increased likelihood of incident depression in fully adjusted models, with odds ratios of 1.54 (95% CI = 1.08-2.19) and 1.54 (95% CI = 1.01-2.35), respectively. Measures of step width and double support time were not associated with depression. CONCLUSIONS: This study demonstrates that older people with incident depression have significantly slower gait speed and shorter step length at initial assessment. These findings are clinically significant given the impact both conditions have on functional status in later life, as well as the possibility that gait problems may represent a potentially modifiable risk factor for depression.
PUBLISHED
doi:10.1111/jgs.15783
Keywords: gait, depression, aging; Ageing